My sister, my best friend - Ismail, Fathiyah; Harun, Nur Syikri (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
The bond that I've with my sister is something beyond words can say. Maybe because I'm the only sister she has, it makes the relationship quite something and special. You name the mood, name the situation, I'll simply reach my sister to share everything. She hasn't met most of my friends, but it seems that she remembers and knows every one important and significant in my life. Actually, there're many moments we've shared. But there're a few that're so clear in my mind. Back in 1999, the new semester begun. Internet was still something so new. Course registration was still conducted manually, where we had to fill in the registration form.